HERMITS AND SYMPOSIASTS. RYSZARD PRZYBYLSKI AND TADEUSZ RÓŻEWICZ – LETTERS, POEMS, AND CONVERSATIONS - Hobot-Marciniak, Joanna (Prace Polonistyczne, 2022)
The article examines the relationship between Tadeusz Różewicz and Ryszard Przybylski, a friend of the poet and an accomplished critic of his works. It analyzes descriptions of their conversations and feasts, as depicted in Tadeusz Różewicz’s poem tempus fugit as well as in the correspondence that was exchanged over the years by these two masters – masters who saw each other as symposiasts as well as old sage hermits who can save the spiritual and cultural heritage of our civilization.